2009
DOI: 10.1021/ie9004404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bitumen Colloidal Nature on the Design of Isocyanate-Based Bituminous Products with Enhanced Rheological Properties

Abstract: This work deals with the influence that bitumen colloidal nature exerts on the rheological properties of bitumen samples modified by isocyanate-based reactive polymers. Shear rheology tests, modulated differential scanning calorimetry (MDSC), chemical characterization by TLC-FID, and AFM microstructural analysis were carried out on four different 150/200 penetration neat bitumen samples and the corresponding MDI-PPG (a low molecular weight polypropylene glycol functionalized with a polymeric 4,4′-diphenylmetha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 21 publications
0
36
0
3
Order By: Relevance
“…However, if temperature is further increased, tanδ is also seen to experience an exponential increase (not shown in the temperature interval studied in Figure 3) as expected from the terminal region. Interestingly, the transition above disappears after water addition or long curing [26,27].…”
Section: In-service Performance Of the Modified Bitumensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if temperature is further increased, tanδ is also seen to experience an exponential increase (not shown in the temperature interval studied in Figure 3) as expected from the terminal region. Interestingly, the transition above disappears after water addition or long curing [26,27].…”
Section: In-service Performance Of the Modified Bitumensmentioning
confidence: 99%
“…Figure 7 shows the evolution of the "modified" colloidal index values for the modified binders studied. According to the C.I.mod defined above and to the bitumen colloidal model, a higher index value would be related to a material which exhibits a more significant solid-like behaviour [20,23,26,27]. Longer curing times, above all after only 1h of processing, enhance the material's microstructure (larger quality of its colloidal microstructure or a more solid-like behaviour).…”
Section: Chemical Modification and Microstructurementioning
confidence: 99%
“…However, the material hardens with time. Even though ''fresh'' emulsions can satisfactorily perform as such from the very first moment (compare the large differences in viscosities, at 60ºC, for neat bitumen and residues in Figure 5), Carrera et al (2009) demonstrated that in-service curing makes these binders evolve towards a better performance against the permanent deformation. In contrast, manufacturing of emulsions with other PMBs may be especially delicate, as processing temperature has to be very high for the PMBs to have a viscosity of about 200 mPa·s (Lesueur 2011).…”
Section: Rheology Of the Emulsion Residuesmentioning
confidence: 99%
“…In order to resolve these problems, we propose to conduct a reactive modification with an isocyanate-functionalized polypropylene glycol, a liquid with low viscosity which allows both mixing with bitumen and further emulsification to be carried out between 80 and 90ºC in an open vessel. This prepolymer has shown to produce an important increase in the binder viscosity as a consequence of ambient curing once in service (Carrera et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Other no-common additives employed in the bitumen modification are waste polymer [7,8] (plastic from agriculture, crumb tyre rubber, etc. ), sulphur [9] or polyurethanes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%